Expressão gênica diferencial de laranja Pêra Rio (Citrus sinensis (L.) Osbeck) e Lima Ácida 'Galego' (Citrus aurantifolia Swingle) em resposta à infecção por Xanthomonas citri subsp. citri - Cavallini, Juliana da Silva [UNESP] (2013)
The citrus agribusiness is very important to the Brazilian economy, but the increase of diseases in the last decade has caused great economic losses to the sector. The citrus canker, caused by the bacterium Xanthomonas citri subsp. citri (Xac), is a serious disease that attacks all citrus species economically important worldwide and there is not an effective method for its control. In this study, RNASeq was used to analyze the transcriptional profiles of two contrasting citrus genotypes regarding citrus canker susceptibility: sweet orange Pêra Rio (PR), moderately resistant, and Mexican lime ‘Galego´ (ML), highly susceptible. Gene expression were performed in a HiScanSQ System (Illumina) using total RNA isolated from leaves collected 24, 48 and 72 hours after Xac inoculation, with leaves inoculated with water been used as control. It were found 6,330, 3,478 and 6,795 differentially expressed genes (DGEs) in moderately resistant PR specie at 24, 48 and 72 hours after Xac inoculation, respectively, when compared with their controls. In the specie highly susceptible ML, it was identified 1,491, 5,621 and 2,145 DGEs after 24, 48 and 72 hours after Xac inoculation, respectively. Through the program Blast2GO, genes and metabolic pathways related to photosynthesis, cell signaling, hormone synthesis, transcription factors, among others, were found as involved in plant defense. This study revealed differences at the molecular level between PR and ML in response to citrus canker, showing that in the specie moderately resistant there is a greater activation of host defense mechanisms. Such informations can be used for the development of citrus plants with an adequate level of resistance to citrus canker